Scintillation modelling from satellite to earth link at Ku Band - Nadirah Binti Abdul Rahim (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
Fast evolution in new satellite services, for instance VSAT for internet access, LAN interconnection, multimedia applications has triggered an increasing demand of bandwidth usage for satellite communications. But, these systems are susceptible to propagation effects that become gradually significant as the frequency increases. The propagation measurements at frequencies above 10 GHz have been carried out widely in the temperate climatic region where most of the advanced and established countries are situated. This is different in the tropical countries where the data coverage for these countries are insufficient, even though they have much more complex and unpredictable climatic behavior compared to the temperate region.Scintillation is the rapid signal fluctuations of amplitude and phase of a radio wave which is significant in tropical climate. This thesis presents the data analysis of the tropospheric scintillation for satellite to earth link at Ku-band. 12 months (January 2011 till December 2011) data were collected and analyzed to evaluate the effect of tropospheric scintillation. The measured scintillation statistics were subsequently compared against six scintillation prediction models which include Karasawa, ITU-R, OTUNG, Van de Kamp, Ortgies-T and Ortgies-N. The findings show that the Ortgies- N has the lowest RMS error for the scintillation fades, with 34.3% whereas Van de Kamp has the lowest RMS error for the scintillation enhancements with 39.2%. The statistics were then further analyzed to inspect seasonal, worst-month, diurnal and rain induced scintillations. The scintillation studies are essential especially when predicting link quality for particular types of services. For instance, to fully evaluate the influence of scintillations on certain types of digital services, it is required to identify not only the total fade time but also the distribution of the durations of the individual fades. By using the measured scintillation data, a modification of the Karasawa model for scintillation fades and scintillation enhancements is proposed based on data measured in Malaysia.